Kuttner tumor involving minor salivary glands: A very rare case report - Vinay Kumar Reddy Kundoor; Moni Thakur; Venkateswara Rao Guttikonda; Ramesh Thummala (Wolters Kluwer Medknow Publications, 2014)
Kuttner tumor, also known as chronic sclerosing sialadenitis, was first described by Dr. H. Kuttner in 1896. It is an uncommon, chronic, benign tumor-like lesion predominantly involving the submandibular glands of middle-aged individuals, and presents as a firm, painful swelling. Histologically, it is characterized by progressive periductal sclerosis, acinar atrophy, and gland infiltration by lymphocytes. A case of Kuttner tumor involving the minor salivary glands is reported.